2001
DOI: 10.1016/s0167-4889(01)00082-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of phospholemman expression decreases osmosensitive taurine efflux in astrocytes

Abstract: The role of phospholemman (PLM) in taurine and Cl(-) efflux elicited by 30% hyposmotic solution was studied in cultured cerebellar astrocytes with reduced PLM expression by antisense oligonucleotide (AO) treatment. PLM, a substrate for protein kinases (PK) C and A, is a protein that increases an anion current in Xenopus oocytes and forms taurine-selective channels in lipid bilayers. Taurine contributes as an osmolyte to regulatory volume decrease (RVD) and is highly permeable through PLM channels in bilayers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…Using rather high concentrations (10 M) of AS oligonucleotides directed at the start codon or at nucleotides ϩ22 to ϩ46, Moran et al (12) demonstrated PLM downregulation in astrocytes by 40.5% and 27.2%, respectively, after 24 h of PLM AS oligonucleotide exposure. In addition, the regulatory volume decrease was markedly impaired in PLMdownregulated astrocytes (12), consistent with the ion channellike behavior (10), channel regulatory role (16), and osmotic regulatory function (11) ascribed to PLM in noncardiac tissues. In the present study, we did not use the AS oligonucleotide approach because it is well known that uptake of naked DNA by adult cardiac myocytes is a very inefficient process (8) and because we (19) have previously demonstrated that exposure to only 1 M of AS oligonucleotides (to NCX1) resulted in toxicity to adult rat cardiac myocytes.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Using rather high concentrations (10 M) of AS oligonucleotides directed at the start codon or at nucleotides ϩ22 to ϩ46, Moran et al (12) demonstrated PLM downregulation in astrocytes by 40.5% and 27.2%, respectively, after 24 h of PLM AS oligonucleotide exposure. In addition, the regulatory volume decrease was markedly impaired in PLMdownregulated astrocytes (12), consistent with the ion channellike behavior (10), channel regulatory role (16), and osmotic regulatory function (11) ascribed to PLM in noncardiac tissues. In the present study, we did not use the AS oligonucleotide approach because it is well known that uptake of naked DNA by adult cardiac myocytes is a very inefficient process (8) and because we (19) have previously demonstrated that exposure to only 1 M of AS oligonucleotides (to NCX1) resulted in toxicity to adult rat cardiac myocytes.…”
Section: Discussionsupporting
confidence: 74%
“…To our knowledge, there has only been one published study (12) on the downregulation of PLM in neonatal rat cerebellar astrocytes. Using rather high concentrations (10 M) of AS oligonucleotides directed at the start codon or at nucleotides ϩ22 to ϩ46, Moran et al (12) demonstrated PLM downregulation in astrocytes by 40.5% and 27.2%, respectively, after 24 h of PLM AS oligonucleotide exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, both when expressed in oocytes or added to lipid bilayers, PLM selectively transports the zwitterionic amino acid taurine (22), an osmolyte of animal cells. Recently, it was also shown that PLM stably transfected in HEK cells increases taurine efflux and regulatory volume decrease in response to cell swelling (39) and that in astrocytes taurine efflux can be inhibited after a decrease in the expression of endogenous PLM by antisense oligonucleotide (40). Thus, based on its function as a channel or a channel regulator, it is believed that PLM plays a specific role in muscle contractility and cell volume regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The astrocytic uptake of both GABA and taurine, another amino acid which is generally regarded as purely inhibitory, is stimulated by β-adrenergic receptor activation, but unaffected by α 1 or α 2 receptor agonists [42]. However, also the release of taurine is enhanced by activation of β-adrenergic receptors, both in bulk-prepared astrocytes [269] and in primary astrocyte cultures [270][271][272]. In the hypothalamo-hypohysial system the basal release of vasopressin and oxytocin from a perifused explant of the anterior lobe of the pituitary is enhanced by taurine [273].…”
Section: Uptake and Release Of Amino Acidsmentioning
confidence: 99%